Asymptotic Behavior of a Parametric Algebraic Surface (Contemporary Mathematics, 2023)
Starting from the concept of infinite branches and approximation surfaces, we present a method to compute infinite branches and surfaces having the same asymptotic behavior as an input parametric surface. The results obtained in this work represent a breakthrough for the study of surfaces and their applications.
Keywords: parametric algebraic surface; infinity branches; convergent branches; asymptotic behavior; approaching surfaces